Al-Maqasid al-Akhlaqiyyah Li Al-Khitab al-Maaly Fi Surah Al-Nisa - Radwan Jamal Yousef Elatrash; Rochmad (Universitas Darussalam Gontor, 2023)
This paper aims to shed light on some of the financial and ethical purposes of Surah Al-Nisa. This Surah had a significant role in transforming the convictions of the pre-Islamic society after many of them became Muslim in not being exposed to the financial transactions of the vulnerable group in the Islamic society through economic and administrative empowerment for them. These verses also come in response to difficult circumstances faced by vulnerable women, orphans, and children and the robbery of their financial rights. This research uses the inductive method to observe the financial verses in Surah Al-Nisa. Then relies on the analytical approach to study and discuss these verses in their moral purposes in Surah Al-Nisa. One of the research's most important findings is that Surah Al-Nisa contains many economic and ethical goals. The first is achieving complete support for the weak in the Muslim community. The first category of these vulnerable people is the orphans; by changing the convictions of parents and guardians and waiving arrogant social restrictions. Furthermore, these verses contain some plans and rehabilitation courses that afflict orphans and the vulnerable to show full awareness to carry out their own interests. In addition, these verses teach how to manage their affairs to obtain independence in financial transactions and not to exercise injustice against them and infringement on their Finance rights and consume it.